PENGARUH HIPNOTERAPI TERHADAP NYERI PADA PASIEN DISPEPSIA DI RSUD dr. R. GOETENG TARUNA DIBRATA PURBALINGGA - Danang Tri Yudhono; Noor Yunida Triana; Madyo Maryoto (Viva Medika, 2014)
Dyspepsia is gastrointestinal disorder which main complaint is pain. Pain management of dyspepsia usespharmacologic and nonpharmacologic techniq. Right pain management technique needed to reducespain efectifly. One of pain management in non-pharmacologic technique is hypnotherapy. The purpose of this study is to know the effect of hypnotherapy in pain management of dyspepsiapatient at Dr. R. Goeteng Taruna Dibrata Hospital Purbalingga. The research using a quasi-experiment with two group pre and post test design and accidentalsampling techniques. The mount of sample was 58 people which determine 2 groups are 29 peoples asintervention group and 29 as control group. To get data uses Visual Analog Scale (VAS) instrument. Thedata analysis used paired t test and independent t test. Result of this study are the youngest age of respondent is 17 years old, the oldest is 50 years old, 62,1% are female patients, the most respondent was graduate from junior high school. Levelpain before intervention is severe pain and after intervention, VAS of hypnotherapy group reducefrom 7, 28 become 3, 28. Therefore at the control group reduce to moderat pain level (VAS from to7, 10 to 6, 28). The t arithmetic in bivariate analysis (10,556) which was greater than t table and sig(0, 00) was smaller than Î± (0, 05). Conclusion is hypnotherapy effect in pain management of dyspepsiapatient at Dr. R. Goeteng Taruna Dibrata Hospital Purbalingga. Key word: hypnotherapy, pain, dyspepsia